Customer Satisfaction and Revisit Intention towards Fast Food Restaurants in Sri Lanka - M. A. K. Sriyalatha; P. J. Kumarasinghe (International Journal of Engineering and Management Research, 2021)
This study aimed at examining factors that effect of food taste, food quality, service quality, perceived price, responsiveness, restaurant environment on customer satisfaction and revisit intention. Data were collected through a structured questionnaire survey of fast food restaurant customers in a selected metropolitan area from Colombo district and students from University of Sri Jayewardenepura. The data were analyzed using SPSS 21.0 and R Studio 3.5.1 software. The study has found that food quality and perceived price are the important antecedents of restaurant customer satisfaction. Further, the results clearly showed a signiﬁcant role of customer satisfaction on revisit intention and crucial impact of perceived price on customer satisfaction. In addition, revisit intention towards the fast food restaurant is directly influenced by food tastes. This study collected data from two selected groups; students from University of Sri Jayewardenepura and one metropolitan area, and data has analyzed further based on demographic characteristics further to confirm the results. Therefore, this study provides valuable insight to restaurant managers on attracting, retaining and satisfying their customers.